Psychotropic Medication Use Increases Risk for Poor Outcomes After Hammertoe Correction Surgery. Issue 4 (16th October 2019) - Maidman, Samuel D.; Erwood, Amalie A.; Brodsky, James; Daoud, Yahya; Fantry, Amanda; Tenenbaum, Shay; Bariteau, Jason T.
Category: Lesser Toes Introduction/Purpose: Hammertoe deformities are common conditions of the lesser toes, known to affect daily activities and cause pain. Following failure of conservative management, surgical correction of these deformities strives to reduce pain and improve physical function. Currently, 1 in 6 Americans are being treated with psychotropic medications. Baseline mental health issues are known to diminish self-perceived overall health and may hamper recovery following surgery. The aim of this study is to assess the impact of psychotropic medication use on the development of complications and reduction of patient reported outcomes following operative hammertoe correction. Methods: Prospectively collected data was reviewed on 116 patients who underwent operative correction of hammertoe deformity following failure of conservative management. Patient demographics, past medical history, and postsurgical complications were recorded from the electronic medical record. Patient-reported outcomes were assessed utilizing preoperative and postoperative Visual Analogue Scale (VAS) and Short Form Health Survey Physical and Mental Component Scores (SF-36 PCS and SF-36 MCS, respectively) with 1-year of follow-up. Data was examined using chi-squared, t-test, and ANOVA analyses. Results: 17.2% of patient were taking only antidepressants, 10.3% other psychotropic medications, and 8.6% both an antidepressant and another psychotropic medication. Wound infections treated with antibiotics occurred in 12.9%. Mean 1-year improvement in VAS, SF-36 PCS, and SF-36 MCS were 2.8 (SE=0.3), 10.8 (SE = 2.0), and 3.1 (SE = 1.3), respectively. A significant association was found between antidepressant use and postoperative superficial wound infection requiring antibiotics (P=0.049). Antidepressant use was also determined to be significantly associated with lower preoperative and postoperative SF-36 MCS (P=0.0023 and P=0.017, respectively). Other psychotropic medication use was significantly associated with lower preoperative SF- 36 MCS (P=0.030) and PCS (P=0.048) as well as postoperative PCS (P=0.023). However, psychotropic medication use was not associated with any reduction in improvement from pre- to postoperatively. Conclusion: Patients receiving psychotropic medications are at an increased risk for developing postoperative infection following hammertoe deformity correction. While these patients at baseline have lower mental and even possible physical component scores, their improvement following hammertoe correction surgery is equivalent to patients not on these medications. Patients treated with psychotropic medications can still benefit from hammertoe correction surgery, but clinicians should recognize the increased risk for complications and expect lower patient-reported outcomes.